Assessment of building operational energy at early stages of design – a monthly quasi-steady-state approach - Santos, P. (2014)
In this paper a new numerical tool to estimate the operational energy of buildings, in early design stages, is presented. This tool is part of a novel approach for life-cycle analysis based on macro-components developed in the European research project SB_Steel – Sustainable Buildings in Steel. Two early design stages are considered in the scope of the methodology: the concept stage and the preliminary stage. This numerical tool enables to estimate the energy use for space heating, space cooling and domestic hot water production, taking into account (i) the climate; (ii) the use type of the building (e.g. residential, offices and commercial/industrial); (iii) the building envelope characteristics; and (iv) the building services. The developed algorithm is based on a monthly quasi-steady-state approach, modified for improved accuracy through the calibration of correction factors that depend on the climatic region and the type of building. Good results were achieved, with errors lower than 10% when compared to performance-based approaches such as the use of advanced dynamic methods. Finally, the case study of a low-rise residential building is presented, in which the results obtained from the simplified methodology are compared with the results from the simulation program EnergyPlus, showing a good agreement between them.